1996
DOI: 10.1001/archsurg.1996.01430190025007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Whole-Body Positron Emission Tomography With [18F]Fluorodeoxyglucose in Identifying Operable Colorectal Cancer Metastases to the Liver

Abstract: The FDG-PET method enabled selection of patients with apparently curable colorectal cancer metastases to the liver for hepatic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
114
1
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(137 citation statements)
references
References 12 publications
6
114
1
16
Order By: Relevance
“…However, for patients with recurrence localized to the liver, there is general agreement that multiple hepatic metastases and the presence of extrahepatic lesions confer an adverse prognosis. 18 F-FDG PET has been shown to be highly accurate in the detection of recurrent and metastatic colorectal cancer (10)(11)(12)(13)(14)(15). A PET scan has comparable sensitivity to a CT scan for the detection of colorectal liver metastases (12)(13)(14) but has superior sensitivity in the detection of extrahepatic disease, compared with CT, and changes the estimation of disease extent in over one third of patients (11,13,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, for patients with recurrence localized to the liver, there is general agreement that multiple hepatic metastases and the presence of extrahepatic lesions confer an adverse prognosis. 18 F-FDG PET has been shown to be highly accurate in the detection of recurrent and metastatic colorectal cancer (10)(11)(12)(13)(14)(15). A PET scan has comparable sensitivity to a CT scan for the detection of colorectal liver metastases (12)(13)(14) but has superior sensitivity in the detection of extrahepatic disease, compared with CT, and changes the estimation of disease extent in over one third of patients (11,13,16).…”
mentioning
confidence: 99%
“…18 F-FDG PET has been shown to be highly accurate in the detection of recurrent and metastatic colorectal cancer (10)(11)(12)(13)(14)(15). A PET scan has comparable sensitivity to a CT scan for the detection of colorectal liver metastases (12)(13)(14) but has superior sensitivity in the detection of extrahepatic disease, compared with CT, and changes the estimation of disease extent in over one third of patients (11,13,16). Several reports also indicate that PET can influence the management of patients with metastatic colorectal cancer (11,(17)(18)(19)(20), but there are few prospective studies (11,17).…”
mentioning
confidence: 99%
“…Several recent studies have demonstrated a high accuracy of fluorine 18-fluorodeoxyglucose (FDG) positron emission tomography (PET) for colorectal cancer. [8][9][10] However, PET is limited by poor resolution and poor anatomic localization of positive PET lesions. To overcome these limitations, PET has been combined with CT. 11 This combination provides simultaneous functional and anatomic information.…”
mentioning
confidence: 99%
“…En los pacientes tratados de una neoplasia colorectal, con la sospecha de recurrencia basada en la elevación sérica del antígeno carcinoembrionario, el cambio de manejo terapéutico provocado por la PET es del 39% y no difiere de los resultados previamente obtenidos por Vitola 20 (25%), Lai 21 (29%), Delbeke 22 (33%), Ogunbiyi 23 (44%) o Valk 24 (31%). Este cambio de actitud terapéutica se explica por una una mayor sensibilidad de la PET con respecto a la TAC en la valoración de la infiltración tumoral del abdomen, la pelvis y el retroperitoneo, así como por su capacidad de detectar enfermedad tumoral en localizaciones pocos habituales (mediastino, hueso y glándulas suprarrenales) 24 .…”
Section: Discussionunclassified